Genetic background influences expression and function of the cation channel TRPM4 in the mouse heart - Medert, Rebekka; Pironet, Andy; Bacmeister, Lucas; Segin, Sebastian; Camacho Londoño, Juan Eduardo; Vennekens, Rudi; Freichel, Marc (Basic research in cardiology, 2020)
Transient receptor potential melastatin 4 (TRPM4) cation channels act in cardiomyocytes as a negative modulator of the L-type Ca2+ current. Ubiquitous Trpm4 deletion in mice leads to an increased β-adrenergic inotropy in healthy mice as well as after myocardial infarction. In this study, we set out to investigate cardiac inotropy in mice with cardiomyocyte-specific Trpm4 deletion. The results guided us to investigate the relevance of TRPM4 for catecholamine-evoked Ca2+ signaling in cardiomyocytes and inotropy in vivo in TRPM4-deficient mouse models of different genetic background. Cardiac hemodynamics were investigated using pressure-volume analysis. Surprisingly, an increased β-adrenergic inotropy was observed in global TRPM4-deficient mice on a 129SvJ genetic background, but the inotropic response was unaltered in mice with global and cardiomyocyte-specific TRPM4 deletion on the C57Bl/6N background. We found that the expression of TRPM4 proteins is about 78 ± 10% higher in wild-type mice on the 129SvJ versus C57Bl/6N background. In accordance with contractility measurements, our analysis of the intracellular Ca2+ transients revealed an increase in ISO-evoked Ca2+ rise in Trpm4-deficient cardiomyocytes of the 129SvJ strain, but not of the C57Bl/6N strain. No significant differences were observed between the two mouse strains in the expression of other regulators of cardiomyocyte Ca2+ homeostasis. We conclude that the relevance of TRPM4 for cardiac contractility depends on homeostatic TRPM4 expression levels or the genetic endowment in different mouse strains as well as on the health/disease status. Therefore, the concept of inhibiting TRPM4 channels to improve cardiac contractility needs to be carefully explored in specific strains and species and prospectively in different genetically diverse populations of patients.
Gesehen am 22.12.2020